2021
DOI: 10.3390/agronomy11122414
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Immersion System for Production of Biomass and Bioactive Compounds from Medicinal Plants

Abstract: The cultivation of medicinal plants and the production of bioactive compounds derived from them are of fundamental importance and interest, not only at the pharmacological level but also in nutraceutical and cosmetic industries and in functional foods, as well as plant protection in agriculture. In order to respond adequately to the increased demands of the global market from a quantitative and qualitative point of view and to guarantee environmental sustainability of the productions, it is necessary to resort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 138 publications
(178 reference statements)
0
7
0
Order By: Relevance
“…Each of the three bioreactors contained 15 plants on MS medium without agar [9][10]. Also, 45 test tube plants were used as control samples.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the three bioreactors contained 15 plants on MS medium without agar [9][10]. Also, 45 test tube plants were used as control samples.…”
Section: Methodsmentioning
confidence: 99%
“…Ptak et al [154] demonstrated the positive influence of metatopolin and benzyladenine on plant development with two times more production of morphologically normal plants from SEs in TIS than SS medium without any hyperhydricity. TIS also helps reduce medium browning due to oxidation, plant contamination through air vents, and lower agitation stress on plant tissues due to the absence of mechanical devices [155,156]. Though TIS is mainly utilized for plant micropropagation, it also offers an alternative to SS and liquid culture for increasing biomass yield and secondary metabolite production at a low cost.…”
Section: Benefits and Drawbacks Of Tismentioning
confidence: 99%
“…Studies have indicated that it facilitates faster plant multiplication and is more effective for producing certain secondary metabolites compared to plants grown in soil [ 5 , 13 , 14 , 15 , 16 ]. The key aspect for maximizing the potential of in vitro cultures maintained in the PlantForm TIS is the experimental optimization of process parameters [ 4 , 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%